Mechanical response of the real tree root architecture under lateral load - Ramos-Rivera, Johnatan (2022)
The impact of climate change on tree stability is often associated with a higher risk of windthrow due to higher frequency and greater magnitude of extreme climatic conditions. Higher lateral loads due to an increase in maximum wind and rainfall reduce tree anchorage because of a decrease in soil matric suction and consequently the overall strength in the system of trunk, root, and soil. This study compared the mechanical response of trees with different root architectures using static loading tests conducted in the field and numerical analysis of laser-scanned root systems. For this case, mature trees of Khaya senegalensis (Desr.) A. Juss., Samanea saman (Jacq.) Merr., and Syzygium grande (Wight) Wight ex Walp. were tested and analyzed. The root system models consisted of root system architectures obtained using 3-D laser scanning. A parametric analysis was conducted by varying the modulus of elasticity of the soil (Es) from 2.5 to 25 MPa, and the results were compared with those of the static loading tests to obtain the overall mechanical responses of the root–soil systems. The results showed important dependencies of the mechanical responses of the root–soil system on the root architecture in withstanding the lateral load. The numerical models also allowed estimation of the effective leeward and windward anchorage zones with different soil elastic moduli and rooting architectures to define the extent of the tree root protection zones. Key words: Numerical modelling, soil-structure interaction, anchorage strength, tree root stability.